Social Acceptance and Generative AI Brands. The Case of OpenAI - Adamo , Giorgia (E|C, 2024)
The delicate relationship between humans and non-humans is being challenged by the unstoppable entry of generative platforms in the market, able to deeply transform the meaning of creative production and elicit divided reactions from society. Drawing upon a sociosemiotic approach in dialogue with Bruno Latour, this contribution wants to analyze the discursive strategies deployed by the brand OpenAI to mitigate consumers’ anxieties in adopting these devices, reflecting the intricate and problematic relationship between society and non-humans in today’s world. As a final step of the work, an analysis of user comments was conducted with the aim of evaluating to what extent the brand was able, through its narratives, to effectively communicate a harmonious coexistence between humans and non-humans.